2022
DOI: 10.3389/fphys.2021.790347
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Basal Metabolic Rate and All-Cause Mortality in a Prospective Cohort of Southern Chinese Adults

Abstract: Objective: The aim of this study was to assess the relationship between basal metabolic rate (BMR) and all-cause mortality in southern Chinese adults.Methods: We prospectively examined the relationship between BMR and all-cause mortality in 12,608 Southern Chinese adults with age ≥ 35 years who participated in the National Key R&D Program from 2013–2014 to 2019–2020. Cox proportional hazard models were used to examine the association between BMR and all-cause mortality.Results: A total of 809 deaths (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…The results of this study show that BMR decreases nonlinearly with age, and the rate of decline accelerates with age, which is consistent with previous research (37). In the adult population in southern China, the increase in BMR was independently and negatively correlated with all-cause mortality among elderly male subjects (38); in particular, this is the first study to show that reduced BMR is an important risk factor for death among elderly individuals. In contrast, longlived people can maintain low-energy metabolism (39-41).…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study show that BMR decreases nonlinearly with age, and the rate of decline accelerates with age, which is consistent with previous research (37). In the adult population in southern China, the increase in BMR was independently and negatively correlated with all-cause mortality among elderly male subjects (38); in particular, this is the first study to show that reduced BMR is an important risk factor for death among elderly individuals. In contrast, longlived people can maintain low-energy metabolism (39-41).…”
Section: Discussionsupporting
confidence: 91%
“…65-70 years of age. In a Chinese cohort aged above 60 years at the onset of the study (Han, Hu et al 2022), the decrease in the basal metabolic rate markedly accelerated after 6 years of follow up. Agespeci c world records in different track-and-eld and weight-lifting disciplines decrease more rapidly at ages above 70 than before (Berthelot, Bar-Hen et al 2019).…”
Section: Discussionmentioning
confidence: 96%
“…Observational studies have suggested that higher BMR predicts mortality in young individuals 8 , 9 but lower mortality in old individuals 10 . Somewhat counter-intuitively, associations that change with age at recruitment may indicate causality because each successively older age group are more strongly selected survivors of a harmful exposure 11 .…”
Section: Introductionmentioning
confidence: 99%
“…A study in mice suggested that the observational association of BMR with lifespan could be confounded by fat mass 12 . Notably, body composition was not adjusted for in some of the human studies assessing the association of BMR with mortality 9 , 10 . Some forms of physical activity, such as resistance training but not aerobic exercise, have been shown to increase BMR 13 , but cannot be comprehensively assessed and adjusted for adequately, as seen in previous human studies on the same topic 9 , 10 , 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation